CAPM, INDEKS TUNGGAL DAN TREYNOR SEBAGAI ANALISIS PORTOFOLIO PADA SAHAM SYARIAH - Setyowati, Ery Indah; Husnurrosyidah, Husnurrosyidah (KEUNIS, 2021)
This study aims to analyze the optimal portfolio of stocks using a single index model and the Capital Asset Pricing Model (CAPM) in making investment decisions as well as the expected profit and risk of the optimal portfolio formed on Islamic stocks in the Indonesian Sharia Stock Index (ISSI) on the Indonesia Stock Exchange. 2016-2020 period. This research design is descriptive quantitative research. The study population was all stocks that were consistently included in the Indonesian Sharia Stock Index (ISSI), amounting to 207 stocks. The number of samples of this study was 136 stocks using the Slovin method. The results show that there are 54 stocks that meet the criteria for optimal portfolio formation. The optimal portfolio of ISSI index stocks has a portfolio return rate of 21.95% and a portfolio risk of 10.49%. The portfolio performance based on the Treynor index shows that the best of the 54 stocks is PTSP shares amounting to 32.73% of the trading sector. While the results in determining investment decisions using the Capital Asset Pricing Model (CAPM) method and 136 company shares, there are 65 undervalued stocks, and 71 stocks are overvalued.